2010
DOI: 10.1007/s00221-010-2275-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Müller-Lyer illusion on saccades is modulated by spatial predictability and saccadic latency

Abstract: Studies investigating the effect of visual illusions on saccadic eye movements have provided a wide variety of results. In this study, we test three factors that might explain this variability: the spatial predictability of the stimulus, the duration of the stimulus and the latency of the saccades. Participants made a saccade from one end of a Müller-Lyer figure to the other end. By changing the spatial predictability of the stimulus, we find that the illusion has a clear effect on saccades (16%) when the stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…This could have influenced the results. We know that eye movements have a strong influence on susceptibility to the Müller-Lyer illusion (e.g., de Grave & Bruno, 2010;van Zoest & Hunt, 2011) and that people with and without ASD differ in the way they scan visual scenes (Pelphrey et al, 2002). It then follows that perhaps the effects on the Müller-Lyer illusion observed by Chouinard et al (2013) Walter et al (2009) argued that greater levels of systemising meant a greater focus on details, which in turn reduced abilities in global integration and levels of susceptibility to some of their illusions.…”
Section: Earlier Research On Illusion Susceptibility As a Function Ofmentioning
confidence: 99%
“…This could have influenced the results. We know that eye movements have a strong influence on susceptibility to the Müller-Lyer illusion (e.g., de Grave & Bruno, 2010;van Zoest & Hunt, 2011) and that people with and without ASD differ in the way they scan visual scenes (Pelphrey et al, 2002). It then follows that perhaps the effects on the Müller-Lyer illusion observed by Chouinard et al (2013) Walter et al (2009) argued that greater levels of systemising meant a greater focus on details, which in turn reduced abilities in global integration and levels of susceptibility to some of their illusions.…”
Section: Earlier Research On Illusion Susceptibility As a Function Ofmentioning
confidence: 99%
“…There is ample evidence that when we make a saccade from one endpoint of the shaft of a Müller-Lyer figure to the other, our eyes land further from the starting point for the fins-out configuration of the figure (>–<) than for the fins-in configuration of the figure (<–>) for the same length of the shaft [18]–[23]. The reason for this is that information about the distance that is to be moved is used to plan saccades [24][26], so since the misjudged distance between the two endpoints of the Müller-Lyer figure is used to plan the saccade, the illusion influences the saccade amplitude [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the pattern of results found here might not hold for other sensory-motor systems such as those that subserve hand-related actions. Regarding the question of whether the oculo-motor effects found here are based entirely on attention shifts, it is notable that previous studies have shown reduced effects of visual illusions on saccade amplitudes with full attention [17]. In a study of Muller-Lyer illusion [17], it was reported that illusion effects on eye movement were largest for fast compared to longer saccadic latencies.…”
Section: Discussionmentioning
confidence: 64%
“…Regarding the question of whether the oculo-motor effects found here are based entirely on attention shifts, it is notable that previous studies have shown reduced effects of visual illusions on saccade amplitudes with full attention [17]. In a study of Muller-Lyer illusion [17], it was reported that illusion effects on eye movement were largest for fast compared to longer saccadic latencies. Longer latencies result in a smaller illusion, suggesting that with sufficient time the oculomotor system was able to determine an accurate position of the target.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation